European Union policy towards Free Trade Agreements - Stephen Woolcock (European Centre for International Political Economy (ECIPE), 2007)
The European Union has recently shifted to a trade policy that envisages a greater use of Free Trade Agreements (FTAs). In particular the EU is working on a number of new FTA initiatives. Policy statements also reiterate the EU's commitment to multilateralism in trade and to the completion of the stalled Doha Development Agenda. This paper considers the background to the shift towards a more active use of FTAs, the motivations and forces that have brought about the shift in policy, and the likely EU objectives with regard to the content of the FTAs. Unlike the US the EU has no "model FTA" to form the basis of negotiations with all partners. In assessing the outlines of the EU negotiating mandates for these new FTAs it is, however, possible to also draw on recent policy statements and the studies and reports produced on each possible new FTA. Finally, the paper discusses whether the EU can reconcile this greater emphasis on bilateral FTAs with its commitment to multilateralism in trade.
Keywords: F02; F13; F53; P59; 330; Trade Policy; Free Trade Agreements; International Political Economy